Can a Calibrated New-Keynesian Model of Monetary Policy Fit the Facts? - Ulf Söderström; Paul Söderlind; Anders Vredin (Sveriges Riksbank, 2002)
Using an empirical New-Keynesian model with optimal discretionary monetary policy, we calibrate key parameters - the central bank's preference parameters; the degree of forward-looking behavior in the determination of inflation and output; and the variances of inflation and output shocks - to match some broad characteristics of U.S. data. Our preferred parameterizations all imply a small concern for output stability but a large preference for interest rate smoothing, and a small degree of forward-looking behavior in pricesetting but a large degree of forward-looking in the determination of output. We provide some intuition for these results and discuss their consequences for practical monetary policy analysis.
Keywords: E52; E58; 330; Interest rate smoothing; central bank objectives; forward-looking behavior